THE EFFECT OF TECHNOLOGY-BASED LEARNING ON IMPROVING EDUCATIONAL COMMUNICATION SKILLS OF ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTS - Yoga Pratama (CV. RADJA PUBLIKA, 2025)
This study aims to determine the influence of technology-based learning on improving the educational communication skills of students of the Elementary School Teacher Education Study Program (PGSD). Using a descriptive quantitative approach with a simple linear regression survey and analysis method, this study involves students who actively participate in technology-based lectures. The instrument used was in the form of a closed questionnaire that measured two main variables: the intensity of technology use in learning and students' communication skills. The results show that students with a high level of technology utilization tend to have better communication skills. Data analysis showed a significant influence between technology-based learning on communication skills, with a significance value of 0.003 and a coefficient of determination (R²) of 0.452. These findings support Vygotsky's theory of constructivism and Garrison's theory of social presence, that technology-mediated social interactions play an important role in the development of communication competence. Technology-based learning has been proven to be able to create a learning environment that supports the development of students' communication skills effectively and is relevant to the demands of 21st century education.